Bauran Pemasaran (Marketing Mix) Syari’ah - Aprilia, Fania; Faricha, Risalatul; Ahla, Hilwiyatul; Rahayu, SE., MM, Dr. Yayuk Sri (Maliki Interdisciplinary Journal, 2025)
Marketing is a key element of business success both domestically and internationally, and plays an important role in product and sales strategy. Modern marketing concepts focus not only on price and quality, but also on creative and innovative strategies. In the Sharia context, marketing is defined as activities that are based on Islamic ethical values ​​such as honesty, transparency and social responsibility. This jurnals explains the implementation of the Sharia Marketing Mix (Marketing Mix). This includes product, price, promotion, location, and additional factors such as process, physical evidence, and service. Sharia marketing principles emphasize moral and spiritual values, such as equal relationships and healthy competition between businesses and consumers. Sharia marketing strategies include differentiation, implementation of the marketing mix, and contract sales, which are legal according to Islamic law. The case study at Baitul Mal wat Tamwil (BMT) illustrates the importance of a collaborative approach, transparency and collaboration with stakeholders. Sharia marketing which is based on Islamic values ​​does not only aim to obtain economic profits, but also contributes to the welfare of society. This document provides a comprehensive guide to integrating Sharia principles into modern marketing activities.